Analysis of administrator and curator fees from the perspective of debtors and creditors - Fadilla Jamila; Sakka Pati; Melantik Rompegading (LEGAL BRIEF, 2022)
Bankruptcy law recognizes two mechanisms, namely suspension of debt payment obligations (PKPU) and bankruptcy. In PKPU mechanism, administrators work with the debtor to manage the debtor's assets, while in bankruptcy curators manage and settle bankrupt assets. Based on article 18 (5) and article 234 (5) Law No.37 of 2004, payment of administrator and curator fees takes priority and is charged to the debtor. It raises issue regarding justice principle. This paper will discuss the administrator and curator fees from debtor and creditor’s perspectives. This study uses normative juridical method with a conceptual and statutory approach. The research found that the amount of administrator and curator fees has undergone improvement, for instance it has reduced the maximum threshold. However, the provision that administrator fees borne by the debtor who  experienced financial difficulties will burden the debtor, particularly if PKPU was not initiated by the debtor. Should the PKPU ends in bankruptcy, the debtor will not only be burdened with administrator fees, but also curator fees. Meanwhile, from the perspective of creditors, the payment of administrator and curator fees can certainly affect creditors' payment, especially concurrent creditors who do not hold collateral and have no privilege to receive priority payments.